Kearifan Lokal Masyarakat Urang Kanekes (Baduy) untuk Ketahanan Pangan Masyaraat dan Kontribusinya untuk Ketahanan Pangan di Kabupaten Lebak dan Provinsi Banten - Fahruqi, Muhammad Nur; Moeis, Jossy Prananta (https://jurnal.binamandiri.ac.id/, 2024)
For indigenous peoples, agriculture is still the basis of their lives. However, for the Kanekes people, agriculture is usually used as a ritual to worship their beliefs, so it becomes local wisdom that is the forerunner to the food security of the Kanekes people. This research aims to determine local wisdom, a determining factor in Urang Kanekes (Baduy) food security, and its contribution to food security in Lebak Regency and Banten Province. Using a mix-method for a qualitative approach to Urang Kanekes' local wisdom, producing the central system of huma rice farming, which is stored in Leuit, is local wisdom that plays a role in food security, and apart from farming, he sells honey, durian, brown sugar, and becomes a tour guide who visits Kanekes. The quantitative approach uses regression with Lebak Regency and provincial-level data. First, panel data regression for 28 subdistricts in Lebak Regency for 12 months from 2020-2021 shows that Leuwidamar Subdistrict, where Urang Kanekes is located, has a higher rice stock than the average for other subdistricts in Lebak Regency, for every month throughout the year. Second, multiple regression was applied to 4 food indices (security, availability, affordability, and usefulness) with data from 8 regencies/cities in Banten Province between 2018-2021. The research results show that local wisdom through farming and storing it in barns is an essential pillar of food availability for a community, in this case, the Urang Kanekes community, where food security at the community level will contribute to subsequent levels up to the national level.